Review of Frigitilla Williams in Bartholomay et al., 2015, with description of a new species from Panama (Hymenoptera: Mutillidae) - Cambra, Roberto A.; Brothers, Denis J.; Quintero, Diomedes (Zootaxa, 2016)
Frigitilla panamensis Cambra, Brothers & Quintero sp. nov., from Panama, based on females, is described and illustrated. This new species represents the northernmost distribution record for the Neotropical genus Frigitilla Williams in Bartholomay et al., 2015. New synonymy and combination are proposed for Frigitilla simulatrix (F. Smith, 1879), comb. nov. =Mutilla frigidula Cresson, 1902, syn. nov. A lectotype is designated for Mutilla simulatrix F. Smith, 1879. The differentiating characters for the genus are briefly discussed.